How higher-order personal values affect the purchase of electricity storage—Evidence from the German photovoltaic market - Stefan Poier; Anna Maria Nikodemska-Wołowik; Michał Suchanek (Journal of Consumer Behaviour, 2022)
Why do consumers make different decisions even when socioeconomic conditions are similar? The present article examines the effects of human values—as formulations of motivational goals—on the decision to purchase electricity storage for a photovoltaic system, a phenomenon hardly explored in prior research regarding high-priced household investments. About 50 percent of photovoltaic-system owners in Germany are also owners of an electricity storage. This study aims to explore the more deeply rooted motivational factors behind these different decisions to extend our understanding of consumers' decision-making processes regarding energy-efficiency investments. It is based on an online survey of 460 owners of residential photovoltaic systems in Germany in 2019 and focuses on the interplay between higher-order values, purchase decisions, perceived risk, and environmental concern. The analysis of the higher-order values showed direct effects of conservation and self-transcendence and indirect effects of openness to change and self-enhancement, both mediated by perceived risk.
Keywords: 320